2006
DOI: 10.1007/s10529-006-9204-6
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas stutzeri as a novel biocatalyst for pyruvate production from DL-lactate

Abstract: Pseudomonas stutzeri SDM oxidized DL-lactic acid (25.5 g l(-1)) into pyruvic acid (22.6 g l(-1)) over 24 h. Both NAD(+)-independent D-lactate dehydrogenase and NAD(+)-independent L-lactate dehydrogenase were found for the first time in the bioconversion of lactate to pyruvate based on the enzyme activity assay and proteomic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Candida (Torulopsis) glabrata [8,9] and Escherichia coli [10,11] are the primary microorganisms [12]. In addition, strains of Acetobacter [13], Acinetobacter [14], Pseudomonas [15,16] and Pichia [17,18] have been shown to produce high yields of pyruvate from lactate. Eisenberg et al (1997) found that PA produced by methylotrophic yeast transformants in biocatalyst-assisted fermentations also contain lactic acid (LA) and acetic acid (AA), necessitating a multi-component separation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Candida (Torulopsis) glabrata [8,9] and Escherichia coli [10,11] are the primary microorganisms [12]. In addition, strains of Acetobacter [13], Acinetobacter [14], Pseudomonas [15,16] and Pichia [17,18] have been shown to produce high yields of pyruvate from lactate. Eisenberg et al (1997) found that PA produced by methylotrophic yeast transformants in biocatalyst-assisted fermentations also contain lactic acid (LA) and acetic acid (AA), necessitating a multi-component separation [18].…”
Section: Introductionmentioning
confidence: 99%
“…These conversions based on catalase/glycolate oxidase were operated at 5 • C to prolong enzyme activities. Pseudomonas stutzeri can serve as a biocatalyst for the conversion of D/L-lactate into pyruvate, generating about 23 g/L pyruvate at a yield of 0.89 g/g [85]. Another study with P. stutzeri generated 48 g/L pyruvate at a yield of 0.98 g/g after 29 h at a pH of 8 and a temperature of 30 • C [86].…”
Section: Other Biological Methodsmentioning
confidence: 99%
“…Hansenula polymorpha and Pichia pastoris also can express glycolate oxidase for converting l-lactate to pyruvate [8]. Recently, Pseudomonas stutzeri was reported to prepare pyruvate with both NAD-linked lactate dehydrogenase and NAD-independent lactate dehydrogenase [16]. However, there are no reports related to the stains that have been applied into industrial-scale production of pyruvate.…”
Section: Introductionmentioning
confidence: 99%